The Influence of Hot Forming on the Microstructure and Corrosion Behaviour of AZ31B Magnesium Alloys - Juliawati Alias; Nurul Shuhada Shuhada Mohamed; Mahadzir Ishak; Xiorong Zhou; George E Thompson (Universitas Pendidikan Indonesia, 2018)
The influence of the hot forming process of AZ31B wrought and twin roll cast (TRC) magnesium alloy sheets on the microstructure and corrosion behaviour have been evaluated. The corrosion behaviour was investigated by hydrogen evolution experiments in chloride-containing solution. Filiform-like corrosion was predominant attack to the AZ31 magnesium alloys, as observed by in-situ corrosion observation. The intermetallic particle existence and grain structure significantly influenced the corrosion rate. The dendritic structure of the as-cast TRC alloy was severely attacked, revealing that the as-cast alloy was highly susceptible to corrosion. The presence of twins in wrought alloy was found to act as a corrosion barrier, while the increase in grain size showed the high corrosion rate of the alloy.